CONVERGENT AND DIVERGENT ANGLES OF A SOLID-FUEL ROCKET NOZZLE AND ITS INFLUENCES ON THE MOTOR’S THRUST CURVE - Gonini, G. A. J.; Aliano, A.; Moresco, L. T.; Pasquali, I. B.; Oliveira Jr, A. A. M. (Revista de Engenharia Térmica, 2023)
The main goal of this work is to investigate how the angles of a convergent-divergent rocket nozzle influence the thrust curve of a solid-propulsion rocket. The work has been conducted within an academic rocketry team. As there is not clear reasoning on how to define these angles, the present research provides insights on how these geometrical parameters influence the performance of a rocket motor. A 2D-axisymmetric CFD domain is considered, comprising the fluid domain inside and outside the nozzle, to give room for the shock waves to happen and also accommodate the flow. The study comprises a baseline geometry and twelve modified designs, varying the convergent and the divergent angles of the nozzle. Since the convergent diameter must match the chamber diameter, it is fixed. For the divergent diameter, there is no such restriction; therefore, there are two possibilities: a divergent section with the same divergent diameter or with the same length as the baseline. The benchmark thrust curve is generated with a MATLAB code based on solid-fuel modeling and the De Laval theory. The curve is divided into six steady-state simulations, using boundary conditions of mass flow, pressure and temperature at the inlet and pressure and temperature at the outlet. The baseline geometry is simulated in Ansys Fluent and normalized by the MATLAB benchmark. A mesh study selects which mesh and turbulence model to use based on this normalization. The modified geometries are then compared to the baseline. The main quantity of interest is the thrust but quantities such as static pressure and average velocity at the nozzle exit aid the understanding of the changes in thrust.